2004
DOI: 10.5507/bp.2004.012
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan in the Treatment of Hypertension in Patients With Chronic Renal Insufficiency

Abstract: The primary aim of this study was evaluation of the efficacy of telmisartan (angiotensin II receptor blocker- AT(1) blocker) on blood pressure in 10 patients with renal impairment in moderate or advanced stages of renal insufficiency and not dependent on haemodialysis. Its effect on proteinuria, renal function (represented by serum urea, creatinine, glomerular filtration), evaluation of overall therapy compliance in comparison with a previously prescribed angiotensin converting enzyme inhibitors (ACEI) were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
2
7
1
1
Order By: Relevance
“…The patient population also saw a significant reduction in proteinuria [14] . Similar results were found in a trial conducted by Weinbergov á et al that investigated the use of telmisartan in 10 hypertensive patients with diabetic and non-diabetic renal impairment, proteinuria > 1 g/24 h, hypertensive cardiopathy and an intolerance of ACE-I (cough) [15] . After 1 year of treatment with telmisartan, a significant reduction in SBP, DBP and proteinuria was also seen in this study [15] .…”
Section: Treatment Of Hypertensionsupporting
confidence: 74%
See 1 more Smart Citation
“…The patient population also saw a significant reduction in proteinuria [14] . Similar results were found in a trial conducted by Weinbergov á et al that investigated the use of telmisartan in 10 hypertensive patients with diabetic and non-diabetic renal impairment, proteinuria > 1 g/24 h, hypertensive cardiopathy and an intolerance of ACE-I (cough) [15] . After 1 year of treatment with telmisartan, a significant reduction in SBP, DBP and proteinuria was also seen in this study [15] .…”
Section: Treatment Of Hypertensionsupporting
confidence: 74%
“…Similar results were found in a trial conducted by Weinbergov á et al that investigated the use of telmisartan in 10 hypertensive patients with diabetic and non-diabetic renal impairment, proteinuria > 1 g/24 h, hypertensive cardiopathy and an intolerance of ACE-I (cough) [15] . After 1 year of treatment with telmisartan, a significant reduction in SBP, DBP and proteinuria was also seen in this study [15] . The IDNT (Irbesartan Diabetic Nephropathy Trial) also showed that an ARB can prove effective in decreasing the progression of nephropathy due to Type 2 diabetes [16] .…”
Section: Treatment Of Hypertensionsupporting
confidence: 74%
“…A decline in renal function is inevitable in patients with CKD, and whereas ARBs can attenuate such decline, it has been thought that they cannot actually reverse the damage and improve renal function in general. However, some investigators reported that 24‐h Ccr and eGFR were increased slightly by telmisartan treatment [22,34]. We reported previously [17] that 24‐h Ccr increased significantly ( P ≤ 0·01 vs. baseline values) in CKD patients after 6 months of telmisartan treatment.…”
Section: Discussionmentioning
confidence: 64%
“…Unique renoprotective properties of angiotensin II receptor antagonist, which are independent of blood pressure lowering but related to decreased oxidative stress and correction of chronic hypoxia, have been reported [5]. Telmisartan, a highly selective angiotensin II type I receptor antagonist, reduces blood pressure and proteinuria effectively and safely in patients with moderate or advanced-stage renal insufficiency due to various types of nephropathy [6]. Long-term administration of high doses of telmisartan seems to improve the efficacy of the drug to decrease proteinuria and slow progression to end-stage renal failure in nondiabetic hypertensive renal disease [7].…”
mentioning
confidence: 99%